(untitled) (Acta Scientiarum. Biological Sciences, 2023)
Natural fruit pulp is highly appreciated because it retains the flavor and nutrients of the fresh fruit. However, fruit pulp is susceptible to contamination by pathogenic bacteria, mainly because of improper handling and storage. Therefore, this study evaluated and quantified the presence of pathogenic bacteria in fruit pulp sold in São Raimundo das Mangabeiras, Maranhão, Brazil. Two fruit pulp samples each of açaí (A and B), acerola (C and D), cajá (E and F), cashew (G and H), and passion fruit (I and J) were obtained from supermarkets and subjected to the following microbiological analyses: enumeration of mesophilic bacteria using plate count agar; quantification of total (TC) and thermotolerant (TTC) coliforms using the multiple tube technique; qualitative detection of Escherichia coli on eosin methylene blue agar and that of Salmonella on xylose lysine base agar and enteric agar. Mesophilic bacteria were found to grow in all the samples, with the highest value obtained for the acerola pulp (sample D; average: 1.08 x 105 colony-forming units g-1). However, all samples were in accordance with the Brazilian legislation for this parameter. The most probable number of colonies (MPN g-1) of TC and TTC were â‰¥1,100 in açaí (sample A), cajá (sample E), and cashew (sample G) pulps, which is in disagreement with the maximum value allowed. E. coli and Salmonella were not found to grow in the samples evaluated in this study. Collectively, the data indicate inadequate handling and storage in the production chain of fruit pulp sold in the municipality of São Raimundo das Mangabeiras, suggesting that the population in the region is exposed to a probable risk of food contamination.